PERANCANGAN MANAJEMEN STRUKTUR PADA BANGUNAN GEDUNG 5 LANTAI SEKOLAH SD/SMP KRISTEN IMMANUEL KABUPATEN KUBU RAYA - Syahwalitya Fahdila, Sucy; Eka Pratami, safitri; Syafriadi, syafriadi; Purnama, Ikhwan Arief (Jurusan Teknik Sipil Polnep, 2024)
Improving school building facilities and infrastructure is very necessary because of the rapid development in the world of education. Building planning is very influential because it will produce a building that meets the requirements of being sturdy, economical and aesthetic in order to avoid damage to the building. Construction management is a very appropriate solution for planning the needs of cost, quality, time, and human resources as well as Occupational Safety and Health (K3). In planning the management of the Immanuel Elementary/Junior High School Building, Kubu Raya Regency, an analysis of the working drawings used as the object of management planning is carried out first. So that a job description is obtained from the work drawing to analyze cost management, quality management, time management by making a Network Planning using the Critical Path Method (CPM), human resource management, and occupational health safety management. In this write, the author uses data sources in the form of primary data and secondary data. Primary data is in the form of working drawings and field documentation, while secondary data is in the form of 2020 Unit Price Analysis (AHS), work plans and requirements (RKS), laws/government regulations, and literature. Based on the processed data, the final results include the Draft Budget (RAB) of Rp. 13,751,000,000 , the duration of the work is 228 days, project quality management is made an analysis of the quantity of work in which there are specifications for each job in detail and in accordance with existing guidelines and in accordance with standards, Human Resources (HR) results in the highest number of workers a lot for reinforcement work as many as 88 people and at least on the work of installing bolts and anchors, installing 12mm plates and installing 16mm plates on the roof as many as 2 people. Occupational Health and Safety (K3) is the result of risk control and the need for personal protective equipment that is in accordance with standards and needs.